Cooperation in publicly funded reference material production - H. Emteborg; D. Florian; S. Choquette; S. L. R. Ellison; M. Fernandes-Whaley; L. Mackay; P. Mc Carton; U. Panne; S. G. Sander; S.-K. Kim; A. Held; T. Unsinger; et al. (Стандартные образцы)
Emteborg H. et al. Cooperation in publicly funded reference material production. Accred Qual Assur. 2018;23(6):371-377. DOI.org/10.1007/s00769-018-1349-1.